PENGARUH BUDAYA PERUSAHAAN TERHADAP KINERJA KARYAWAN PT. TASPEN (PERSERO) KCU SEMARANG - Andi Aulia Rahman; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2016)
In performing of work activities, corporate culture has affects into efficiency and effectivity in a company. The existing culture in a company will influence the way of employee’s work and also employee behavior in the working environment. PT. TASPEN (Persero) is a company that work on government social employee’s insurance and retirement savings. PT. TASPEN (Persero) has been applied 5 corporate cultures, those are Integrity, Professionalism, Innovative, Competitive, and Growth. This research aims to know the effect of five corporate cultures such as Integrity, Professionalism, Innovative, Competitive, and Growth to employee’s performance. The type of this research based on explanatory research. The population are 71 employee’s at PT. TASPEN (Persero) Branch Office Semarang by using census sampling technique. The result shows correlation of integrity to employee performance is on average at 0,531 correlation score. Determination coefficient (R2) of professionalism to employee performance at 27,7%. Correlation of innovative to employee performance at under average by 0,321. Determination coefficient (R2) of competitive to employee performance is 30%. Then correlation of growth to employee performance is low with correlation score at 0,278. Simultaneously integrity, professionalism, innovative, competitive and growth have a significant influences to employee performance with F count > F table (10,145 > 2,354) with significant score at 0,000 < 0,005.